Analysis of Motor Vehicle Tax Payment Compliance at Samsat Banyumas Regency - Rina Mudjiyanti; Purnadi Purnadi; Susilo Wardani; Ani Kusbandiyah (Innovation Business Management and Accounting Journal, 2022)
The purpose of this study is to analyze whether there is an effect of administrative sanctions, taxpayer awareness, income level, and modernization of the tax administration system on motor vehicle tax compliance (PKB) in Samsat Banyumas. Tax is one sector of state revenue. Motor vehicle tax is one that affects the high level of regional income. The sample in this study were respondents or motor vehicle taxpayers in the Banyumas Regency area. The results of the study of administrative sanctions, taxpayer awareness, income level, and modernization of the tax administration system on motor vehicle taxpayer compliance positively affect motor vehicle taxpayer compliance. Not only income but also supported by taxpayer awareness. Modernization of the tax payment system is a digital transformation from conventional to digital systems to simplify and accelerate tax administration.